Demonstrating prolog usage: Building a simple game program - Wan Ishak, Wan Hussain (2003)
To demonstrate the use of Prolog and how programming in Prolog is easy and efficient, this paper describe an implementation of the game booby-trap, a game similar to Minesweeper found on most personal computers with windows.